Rola starszych w wybranych starożytnych regułach monastycznych - Ościłowski, Krzysztof (Vox Patrum, 2011)
In the ancient Monastic Rules we can find various principles concerning the Community, persons and Monasteries. Among them we can also find some norms that apply to the so called „Elders” or „seniors”. They distinguish themselves from other monks, by being more advanced in the spiritual and ascetic life and because of this they are set as an example to follow for other Monks. For this reason they have rights to special respect from their fellow brothers. That is the first group of „Elders”. The other group of „Elders” contains Monks of venerable age. They occupy an important position in the monastic community and for this reason their advices, instructions, and admonishes are significant and are often treated as the legal rules. In some cases, „the Elders” are treated as substitutes of Superiors, for example: in preaching, in giving permissions, and in rebuking their fellow brothers, as well as superiors. They are also responsible for the formation of novices. The „Elders” were to be respected and those of venerable age were dispensed from certain duties and norms of the Monastic Rule. Summarizing we can say that the role of the „Elders” in the Community was very important from all points of view.